IMPLEMENTATION OF GOOD GOVERNANCE PRINCIPLES IN PUBLIC SERVICES AT THE TEGAL SARI MANDALA III VILLAGE OFFICE, MEDAN DENAI DISTRICT - nunti sibuea (Yayasan Cita Cendikiawan Al Kharizmi, 2026)
This study aims to determine the application of good governance principles in public services at the Tegal Sari Mandala III Village Office, Medan Denai District, and the inhibiting factors. This study utilizes United Nations Development Programme (UNDP) theory, namely the principles of accountability, the rule of law, transparency, and openness. The research method used was qualitative, and data collection techniques were conducted through observation, interviews, and documentation. The results indicate that the implementation of good governance principles at the Tegal Sari Mandala III Village Office is quite good in terms of accountability, the rule of law, transparency, and openness, although obstacles remain, such as delays in service delivery and insufficient information delivery. Other obstacles include inadequate infrastructure, limited human resources, slow bureaucracy, and a minimal budget. Comprehensive improvements in infrastructure, employee training, bureaucratic simplification, and budget increases are needed to ensure the effective implementation of these principles and improve the quality of public services